Effectiveness of caporite to reduce concentration of iron and mangan in Ciliwung river water as raw water PDAM - Nadhila Aulia Dwiputri; Mia Azizah; Nurlela Nurlela (JURNAL SAINS NATURAL, 2021)
The water of the Ciliwung river used as raw water for PDAM Depok contains iron and manganese, which levels were quite high and exceeded the quality standard. The purposes of the research are to determine the effectiveness of caporite to reduce levels of iron and manganese to reach levels that meet the standards of Government Regulation Number 82 of 2001. The sample used in this study was the water of the Ciliwung river used as a source of raw water for PDAM Depok with two different water treatment plant (WTP) locations, location 1 in Legong WTP and location 2 in Citayam WTP. Raw water was taken using a submersible water pump located at the bottom of the Ciliwung river. The analytical method used as a reference for determining iron levels was based on the FerroZine Rapid Liquid Method 1970, and for manganese levels was based on 1- (2-Pyridylazo) -2-Naphthol PAN Method 1977, both methods using the Spectrophotometric method. The results showed that iron and manganese levels were quite high, exceeding the standards of Government Regulation No.82 of 2001 with a maximum standard of iron content is 0.3 mg/L, and a maximum standard of manganese level is 0.1 mg/L. After adding a certain dose of chlorine to Ciliwung river water in the Legong and Citayam WTPs, it was found that chlorine effectively reduced Fe and Mn levels because it was able to reduce levels up to 80% and meet the quality standards.Keywords: Caporite, Iron, Manganese, Ciliwung River, RegulationABSTRAKEfektivitas kaporit untuk menurunkan kadar besi dan mangan dalam air sungai Ciliwung sebagai air baku PDAMAir sungai Ciliwung yang digunakan sebagai air baku PDAM Depok terdapat zat besi dan mangan dengan kadarnya cukup tinggi serta melebihi ambang baku mutu. Tujuan penelitian ini untuk mengetahui efektivitas kaporit dalam menurunkan kadar besi dan mangan sehingga memenuhi standar baku mutu Peraturan Pemerintah Nomor 82 Tahun 2001 untuk kelas 1. Sampel air yang digunakan dalam penelitian ini diambil dari 2 titik lokasi Instalasi Pengolahan Air (IPA) yang berbeda, yaitu  dari IPA Legong dan  IPA Citayam. Sampel air baku diambil dengan menggunakan pompa air submersible (pompa celup) yang berada di dasar sungai Ciliwung. Penelitian dilakukan dengan eksperimen jar test di laboratorium. Metode analisis untuk menentukan kadar besi  mengacu pada FerroZine Rapid Liquid Method tahun 1970 dan mangan berdasarkan 1-(2-Pyridylazo)-2-Napthol PAN Method tahun 1977 dengan menggunakan metode Spektrofotometri. Hasil penelitian menunjukan kadar besi dan mangan yang cukup tinggi hingga melebihi standar yang telah ditetapkan dalam PP No.82 Tahun 2001 dengan kadar Fe maksimal 0,3 mg/L dan kadar Mn maksimal 0,1 mg/L. Setelah dilakukan penambahan bahan kimia kaporit ke dalam sampel air sungai Ciliwung  dari  IPA Legong dan Citayam, dengan dosis 10 mg/L untuk penurunan Fe dan 30 mg/L untuk penurunan Mn dapat efektif menurunkan konsentrasi Fe dan Mn  hingga 80%, dan memenuhi  standar baku mutu yang digunakan.Kata Kunci: Kaporit, Besi, Mangan, Sungai Ciliwung, Baku Mutu